Hubungan Antara Frekuensi Pemberian ASI dengan Kejadian Ikterus Neonatorum Pada Bayi Usia 0-7 Hari di Puskesmas Wangkal: The Relationship Between Frequency of Breastfeeding and the Incidence of Neonatal Icterus in Infants Aged 0-7 Days at the Wangkal Community Health Center - Rafi’ah Badiatur; Iis Hanifah; Homsiatur Rohmatin (Forind Press, 2024)
Neonatal jaundice is a clinical condition in infants characterized by yellow discoloration of the skin and sclera due to excessive accumulation of unconjugated bilirubin. Jaundice will clinically appear in newborns when the blood bilirubin level is 5-7 mg/dL. Breast milk contains nutrients, hormones, elements of immunity, growth, allergy, and anti-inflammation. Nutrition in breast milk includes nearly 200 elements of food substances. The purpose of this study was to find out whether there is a Correlation between the frequency of breastfeeding and the incidence of neonatal jaundice in infants aged 0-7 days at the Wangkal Health Center in 2023. The study design used correlation analysis with a cross-sectional approach. The data collection technique used was observation with 90 respondents using accidental sampling techniques. Data collection includes coding, editing and tabulating, then analyzed manually and by computer with the Chi-Square Test. Results of the study 90 respondents Most the frequency of breastfeeding was carried out frequently by 57 respondents (63.3%) and the incidence of neonatal jaundice in infants aged 0-7 days did not occur jaundice by 55 respondents (61%) obtained P Value: 0.000 and α : 0.05, meaning that H0 is rejected and H1 is accepted so that there is a Correlation between the frequency of breastfeeding and the incidence of neonatal jaundice in infants aged 0-7 days at the Wangkal Health Center in Probolinggo in 2023. It is hoped that knowledge about the frequency of breastfeeding with neonatal jaundice is important in infants aged 0-7 days at the Wangkal Health Center, Probolinggo in 2023. Where it can reduce the prevalence of infant jaundice and increase infant immunity.